Post-modem Philosophical Point of View Towards the Teaching of Thinking - Duoblienė, Lilija (Acta Paedagogica Vilnensia, 2002)
This article deals with the analysis of post-modern philosophy and its influence on contemporary education. This is a field that has not been researched in Lithuania yet. The main task of this article was to investigate post-modern philosophy interpretation of critical and reflective thinking and the method how to teach thinking. The researches of great philosophers (J. F. Lyotard, H. G. Gadamer, M. Oakeshott) and their interpreters (S. Gallagher, S. Parker, R. Usher, R. Edwards) were analysed. Some conclusions were formulated: the post-modern philosophy deals with meanings of discourse, contextuality, deconstruction and identification through difference, relativity, and ambiguity. Meanings of thinking critical/y and reflectively need new evaluation, because they are passe (old-fashioned). Some of the philosophers' say that field of education is very special, so it requires special rules. While dialectical investigation is based on linguistic games and deconstruction, didactic is grounded by assumption, that there is the way of knowledge legitimating. That means, that thinking in the process of education should be supported and controlled according to agreement in advance.
Keywords: Philosophy of education; education; postmodernism; critical and reflective thinking.